Painting as a Literary Form in Naxén Derizí Novel: A Harmony between Textuality and Embodying Art in Literature - Hussein, Bayan Ahmad (Journal of Duhok University, 2019)
Art in general and literature in particular is a natural inspiration.Sense and  human spirit are their source.The relationship of both literature and art in one space is mixing and adapting the problems that are consideredin terms of beauty science signals as perfect creativity.The intention of the writer of this process is to further clarify and reflect the thought and its purpose. The study of this relationship in an academic and applied way in the literature dates back to the end of the Nineteenth century.The narrator in the novel of(Nxen derizi),through a literary –artistic narrative,can embody the main character paintings in  various texts in order to explain and analyze the effectof the creative dimensions of the paintingson the characters.